COGNITIVE DEVELOPMENT IN CHILDREN WITH STUNTING: A REVIEW OF INFECTION HISTORY AND STIMULATION - Nur Ilah Padhila; Rahmat Hidayat; Suci Sinar Sari; Desi Ratnasari (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Stunting is a chronic nutritional problem that affects not only children’s physical growth but also their cognitive development, including concentration, memory, and future academic readiness. Cognitive development in stunted children is influenced by multiple factors, including infection history and parental stimulation. This study aimed to analyze the relationship between infection history and stimulation and cognitive development among stunted children. This study employed an observational analytic design with a cross-sectional approach. It was conducted in the working area of Tamamaung Public Health Center, Makassar, from October to November 2025. A total of 40 stunted children aged 12–42 months were recruited using total sampling. Data were collected through structured interviews with parents using validated and reliable questionnaires. Data were analyzed using univariate analysis and bivariate analysis with the Chi-square test at a significance level of 0.05. Most children were aged 12–24 months (40.0%) and female (72.5%). Moderate infection history was reported in 50.0% of respondents, while high and moderate levels of stimulation were each found in 42.5% of children. More than half of the children (52.5%) demonstrated appropriate cognitive development. Bivariate analysis showed that infection history was not significantly associated with cognitive development in stunted children (p=0.316), whereas stimulation was significantly associated with cognitive development (p=0.017). Children who received higher stimulation were more likely to demonstrate age-appropriate cognitive development than those who received inadequate stimulation. Infection history was not significantly associated with cognitive development among stunted children, whereas stimulation showed a significant relationship. Consistent parental stimulation should be considered an essential strategy to optimize cognitive development in children with stunting.